PENERAPAN KONSEP RE-THINKING TYPOLOGY PADA HUNIAN VERTIKAL UNTUK DEWASA MUDA DI LAHAN BERKONTUR, CISARUA - Bimo Yudhi Santoso; Mieke Choandi (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
This paper describes and analyzes the types or characteristics of typologies as well as proposes a different typological idea for the typology of vertical housing located in contoured and heavily cultured areas for evolving young adults. This provides views and insights into the architectural thought process. Based on learning the existing type as a reference and choosing various typology as prototype and as a reference for analysing the development trend of vertical housing typology as a guide principle to then propose an arhetype. The results of these analysis are proven re-thinking the typology of the vertical housing itself which is integrated with the microhousing typoloogy. Two typologies emerged, providing insight into the aplication of cultural cosmologi and also integrating the contoured site with the project. Keywords:  contour; microhousing; typology; vertical housing AbstrakTulisan ini menjelaskan dan menganalisis tipe atau karakteristik tipologi serta  mengusulkan sebuah pemikiran tipologi yang berbeda terharap tipologi bangunan vertikal yang berada di daerah berkontur dan berbudaya untuk kaum dewasa muda yang sedang berkembang. Makalah ini memberikan pandangan dan wawasan ke dalam proses pemikiran arsitektur. Berdasarkan pembelajaran tipe eksisting sebagai acuan tren perkembangan dan tipologi bangunan hunian vertikal sebagai panduan prinsip, pendekatan pemikiran ulang tipologi untuk menganalisa tipologi yang ada muncul suatu tipologi baru. Hasil dari analisis ini dibuktikan dengan memikirkan ulang tipologi bangunan vertikal itu sendiri yang di integrasikan dengan tipologi rumah mikro. Dua tipologi yang muncul, memberikan wawasan tentang penerapan kosmologi budaya dan juga mengintegrasikan tapak yang berkontur dengan proyek.